Association between small intestinal bacterial overgrowth and beta-cell function of type 2 diabetes. Issue 7 (July 2020) - Yan, Li-hui; Mu, Biao; Pan, Da; Shi, Ya-nan; Yuan, Ji-hong; Guan, Yue; Li, Wang; Zhu, Xiao-yi; Guo, Lei
Aims: Previous studies suggest that small intestinal bacterial overgrowth (SIBO) is associated with type 2 diabetes. However, few studies have evaluated the association between SIBO and beta-cell function in type 2 diabetes. The aim of this study was to evaluate whether beta-cell function was associated with SIBO. Materials and methods: One hundred four patients with type 2 diabetes were included in this study. Based on the presence of SIBO, the patients were divided into SIBO-positive and SIBO-negative groups. Oral glucose tolerance tests were performed. Insulin sensitivity was measured using 1/homeostasis model assessment of insulin resistance (1/HOMA-IR) and the insulin sensitivity index (ISIM). Insulin release was calculated by HOMA-β, early-phase insulin secretion index InsAUC30 /GluAUC30, and total-phase insulin secretion index InsAUC120 /GluAUC120 . Results: Compared with the SIBO-negative group, patients in the SIBO-positive group showed a higher glucose level at 120 minutes, HbA1c, 1/HOMA-IR, and ISIM and a lower HOMA-β level, early-phase InsAUC30 /GluAUC30, and total-phase InsAUC120 /GluAUC120 . Multiple linear regression analysis showed that body mass index, glucose at 0 minutes, and SIBO were independently associated with the early-phase and total-phase insulin secretion. Conclusion: SIBO may be involved in lower levels of insulin release and worse glycemic control.